Publication ethics of human studies in the light of the Declaration of Helsinki – a mini-review - Sawicka-Gutaj, Nadia; Gruszczyński, Dawid; Guzik, Przemysław; Mostowska, Adrianna; Walkowiak, Jarosław (Journal of Medical Science, 2022)
The Declaration of Helsinki is a set of ethical principles to be followed by scientists involved in medical research with humans or human cells and tissues. This Declaration defines how scientific research should be planned, conducted, documented, analysed, and published. We summarise and discuss some ethical issues related to publishing original articles, including clinical trials, review papers, and case reports based on the seventh revision of the Declaration of Helsinki. The principles of the Declaration of Helsinki refer primarily to the publication of medical research results, in particular clinical trials, as original articles. Such papers are required to meet several ethical requirements, particularly the study protocol transparency and the presentation of the results. In terms of case reports, the bioethical aspects related to their publication are twofold - they need to include informed and voluntary consent and the confidentiality of study participants. The review papers are of the least bioethical concern. However, whether patients' agreements with specific studies are valid if the data are used in meta-analyses is uncertain. Adherence to ethical policies and standards helps to ensure the highest possible quality of scientific publications. Responsibility for compliance with the Declaration of Helsinki lies not only with the authors preparing their manuscripts, but also with the editorial board and reviewers, who must evaluate the ethical soundness of the submitted papers. The additional guidelines for the different types of studies facilitate the implementation of the Declaration principles.